Investigation Some Electromagnetic Characteristic of Pm Synchronous Motor in Flux Weakening Operation - Szénásy, I. (Acta Technica Jaurinensis, 2013)
The power factor, the hysteresis losses and the stator eddy current losses are electromagnetic features of permanent magnet synchronous motors. The newer method for control these motors is the flux weakening operation for extending the region over nominal speed but by nominal voltage. This paper deals with these questions and its impacts.